PENGARUH PENAMBAHAN KROMIUM DAN TEMBAGA TERHADAP KEKUATAN LELAH BESI COR KELABU - Suprihanto, Agus; Suratman, Rochim (ROTASI, 2006)
The mechanical properties of grey cast irons can be modified with alloying elements. Cr and Cu have beenknown as elements that can improve tensile strength of grey cast irons. The improvement of tensile strength can beinfluence of fatigue strength. The goal of this research is to study the effect of alloying Cr and Cu on the fatiguestrength.Four materials of grey cast irons have been conducted to high cycle fatigue testing on the rotating bendingmachine. The first material is grey cast irons without added Cr and Cu, and the other have added. The percentages ofCr have been added are 0,23% wt, 0,32%wt and 0,47%wt and Cu 0,6%wt to 0,7%wt. The metallographyc examinationsand tensile test also have been conducted.The result of this research are the material has the same microstructure. The microstructures of its materials arepearlitic grey cast irons with graphite type VII, distribution A and size of graphite 3-5. The tensile, endurance andfatigue strength of materials, which added Cr and Cu significantly rising, compared with base materials. The tensilestrength rose from 191MPa to 232MPa and the endurance strength raised from 94 MPa to 110MPa. However threemodified materials, which added Cr, and Cu has the same effects.